Dialog Antara Filsafat Pendidikan Barat Dan Nilai Budaya Timur Dalam Pembentukan Karakter Siswa - Suastra, Wayan; Atmaja, Ananta Wikrama Tungga; Tika, I Nyoman (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
This article discusses the interaction between Western educational philosophy and Eastern cultural values ​​in the context of character building for students. By identifying key elements from both educational traditions, this study aims to find common ground that can enrich the educational process in Indonesia. Library methods are used in this study to review the literature from Western educational philosophy and Eastern cultural values ​​to shape the character of students in Indonesia. This study identifies the main principles of both approaches, such as individualism and freedom from the West, and collectivism and social responsibility from the East, and analyzes their potential to complement each other. The result is a theoretical framework that combines both values, creating a holistic character education for students in Indonesia. The result of this work is that the integration of Western educational philosophy with Eastern cultural values ​​in Indonesia is important to form a generation with character and competence. Western philosophy emphasizes the development of individualism and critical thinking, while Eastern values ​​emphasize collectivism and social responsibility. Character education that includes morality and emotional intelligence helps students have integrity, empathy, and social harmony. This holistic educational approach prepares students for academic success while having a strong personality. Policy support and training for educators are needed to teach these values ​​effectively and relevantly.